Bridging Borders: Organizing Short-Term Agricultural Communication Exchange Programs - Emily Rhoades; Roslynn Brain; Ricky Telg; Tracy Irani; Owen Roberts (Journal of Applied Communications, 2006)
This paper describes the efforts of the University of Florida (located in Gainesville, Florida) and the University of Guelph (located in Ontario, Canada, near Toronto) to jointly develop a unique pilot exchange program for undergraduate and graduate agricultural communication students. The program was designed to encourage students to think critically about agriculture, agricultural communications, and culture in each other's countries. During this exchange, nine University of Guelph students traveled to Florida for one week during their winter breaks and six University of Florida students traveled to Canada during their spring breaks. The exchanges took place in back-to-back weeks. Students met with university administrators and agriculture industry representatives, toured agricultural facilities, and visited cultural locations. This paper details the planning process that culminated in the two-week program, provides students' comments about what they learned during the study-abroad experience, and makes recommendations to faculty interested in organizing similar study-abroad programs.